The Effect of Giving Water Extract Boiled Beluntas Leaves on the Prevention of Vaginal Discharge in S1 Public Health Students at the STRADA Indonesia Institute of Health Sciences - Eri Puji Kumalasari; Devy Putri Nursanti; Enjeles Sri Purnama Zet (Universitas STRADA Indonesia, 2024)
Background: The high rate of vaginal discharge in women is caused by infection of various fungi in the vagina by bacteria Thricmonas vaginalis and candida albicans. Excessive and abnormal vaginal discharge can be an early symptom of cervical cancer that can lead to death in women. Purpose: The purpose of this study was to determine the effect of giving water extract of boiled beluntas leaves on the prevention of vaginal discharge in S1 Public Health students at the STRADA Indonesia Institute of Health Sciences. Methods: This study used a pre-experimental method with a type of research one group pre test post test. The population in this study was all S1 Public Health students at the STRADA Indonesia Institute of Health Sciences and sampling using the simple random sampling method with a total of 84 respondents. Data analysis techniques used to test hypotheses are the Wilcoxon Test and data collection using questionnaires. Results: Data analysis using the Wilcoxon test shows that the significance level is 0.000< α = 0.05 so that H0 is rejected and H1 is accepted which means that there is an effect of giving beluntas leaf boiled water extract on the prevention of leucorrhoea in S1 Public Health students at the STRADA Indonesia Institute of Health Sciences. Conclusion: It is expected that female students who experience vaginal discharge can apply water extract of beluntas leaf decoction as a non-pharmacological drug that can be used if experiencing vaginal discharge.